Reflections of Institutional Theory in Mainstream And Turkish Literature: A Cross-Cultural Bibliographic Comparison Between 2014-2025 - MUMCU, ARTÜR YETVART (Türk Kooperatifçilik Kurumu, 2025)
The primary goal of this research was to investigate the manifestations of institutional theory in both the mainstream academic literature and Turkish scholarly literature，and to evaluate the applicability of the theory in different cultural and contextual settings. The research employs a methodology of analyzing 25,052 articles indexed in the Web of Science database together with 1,783 articles obtained from Dergipark. The present study is based on a systematic review and bibliographic analysis of the theory's universal dimensions and its context-dependent variations, as displayed through the network mapping function of VOSviewer. Besides, a trend analysis was performed as a means of tracing the historical progression of publication patterns, while a comparative examination of key terms was executed to mark distinctions between the shared concepts and those found exclusively in each literature stream. The thematic connection mapping through network mapping, the research pinpoints the main research areas within institutional theory in different configurations. The results demonstrate that the divergent nature of Turkish literature in comparison with the mainstream literature dominated the debate on the Relational Progress of Establishing New Institutions and the construction of context-sensitive policies. What is more, the findings also stress the significance of cross-cultural comparisons in revealing how institutional theory remains mostly constant in its basic ideas and principles but adapts to a range of socio- cutural conditions.
Kurumsal Kuramın Ana Akım ve Türkçe Yazındaki Güncel Yansımaları: 2014-2025 Yıllları Arasında Kültürlerarası Bibliyografik Bir Karşılaştırma
Keywords: Institutional Theory; Bibliographic Analysis; Cross-Cultural Comparison; Web of Science